Atrial Fibrillation Is Not Associated With Thromboembolism in Left Ventricular Assist Device Patients: A Systematic Review and Meta-Analysis. Issue 5 (July 2019) - Kittipibul, Veraprapas; Rattanawong, Pattara; Kewcharoen, Jakrin; Chongsathidkiet, Pakawat; Vutthikraivit, Wasawat; Kanjanahattakij, Napatt
Abstract : Atrial fibrillation (AF) is a well-established risk factor of thromboembolism (TE). Thromboembolism is one of the most common complications in patients supported by continuous-flow left ventricular assisted devices (CF-LVADs). However, the association between AF and TE complications in this population is controversial. We conducted a systematic review and meta-analysis to assess the association between AF and overall TE, stroke, and device thrombosis events in CF-LVAD patients. We performed a comprehensive literature search through September 2017 in the databases of MEDLINE and EMBASE. Included studies were prospective or retrospective cohort studies that compared the risk of developing overall TE, stroke, and device thrombosis events in CF-LVAD patients with AF and those without AF. We calculated pooled risk ratio (RR) with 95% confidence intervals (CI) and I 2 statistic using the random-effects model. Eleven studies were included involving 6, 351 patients who underwent CF-LVAD implantation. Overall, TE outcome was available in four studies involving 1, 106 AF and 3, 556 non-AF patients. Stroke outcome was available in seven studies (1, 455 AF and 4, 037 non-AF patients). Device thrombosis outcome was available in three studies (1, 010 AF and 3, 327 non-AF patients). There was no association between AF and TE events (RR = 0.95; 95% CI: 0.57–1.59, I 2 = 79%, p = 0.85), stroke (RR = 1.10; 95% CI: 0.74–1.64, I 2 = 73%, p = 0.65), and device thrombosis (RR = 0.97; 95% CI: 0.56–1.67, I 2 = 42%, p = 0.91). AF in CF-LVAD patients was not associated with overall TE, stroke, or device thrombosis events. These findings might be explained by the highly thrombogenic property of CF-LVADs that exceeds the thromboembolic risk driven by AF. Abstract : Supplemental Digital Content is available in the text.